PERBANDINGAN UJI SITOTOKSIK FRAKSI N-HEKSANA, FRAKSI ETIL ASETAT DAN EKSTRAK PURIFIKASI HERBA SAMBILOTO (Andrographis paniculata (Burm.f.) Nees) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Putu Yudha Ugrasena; Dyah Ratna Ayu Puspitasari; Dewa Ayu Rupayantini (Institut Teknologi dan Kesehatan Bintang Persada, 2022)
Cancer is a disease caused by abnormal growth of body tissue cells, characterized by uncontrolled cell growth. Sambiloto (Andrographis paniculata (Burm.f.) Nees) is known to have anti-cancer activity. One of the preliminary test methods used to determine the potential of sambiloto as an anticancer is the acute toxicity test. The acute toxicity test used was the Brine Shrimp Lethality Test (BSLT). The purpose of this study was to determine the value of LC50% (Lethal Concentration) as the cytotoxic activity of the n-hexane fraction, ethyl acetate fraction and purified extract of bitter herbs. The method used is maceration with 96% ethanol followed by fractionation and purification with n-hexane, ethyl acetate, and water as solvents. Cytotoxic activity test with BSLT using concentration variations of 0, 10, 50, 100, 500, 1000 ppm. The results showed cytotoxic activity based on LC50 values ??for the n-hexane, ethyl acetate, and purified extract fractions, namely 19.9x1012 ppm, 5261,5 ppm, and 83,8 ppm. The results showed that the purified extract of sambiloto herb was very toxic with an LC50 value of 1000 ppm, namely 83.799ppm (p<0.01).